Large wavelength bandwidth Mach-Zehnder modulator based on optical intensity equalization structure - Hu, Heming; Liu, Shiping; Ma, Xiaoyue; Dong, Runyu; Chen, Hua; Fang, Qing (Frontiers in Physics, 2022)
In this paper, we propose a large wavelength bandwidth Mach-Zehnder modulator based on light intensity equalization structure. The modulator is designed into a symmetric structure to increase the optical operating bandwidth. Besides, two auxiliary MZIs are connected to the respective phase shifters of the main modulator to balance the optical intensity in them. Compared with a conventional Mach-Zehnder modulator, this design has a larger optical operating bandwidth over 56.1nm. Besides, the maximum extinction ratio of this modulator is 26.2dB, which is 12dB higher than that of a conventional one. The dynamic extinction ratios at speed of 40Gbps are 4.10dB and 4.02dB in the wavelength of 1530nm and 1560nm respectively. The 3dB electro-optical bandwidth of this modulator under different voltages are almost consistent with the performance of the conventional one. All of these prove that this structural design can effectively increases the performance of Mach-Zehnder modulators.